Effects of Ocean Acidification on Atlantic Cod Larvae (Gadus morhua) - Stiasny, Martina (2017)
Throughout the twentieth and the beginning of the twenty-first century technical advancements in many industries as well as the vast increase in world population have led to increasing emissions of greenhouse gases like carbon dioxide. The changes in the chemistry of the atmosphere not only result in retention of heat causing global warming, but also transfer to the oceans. The world’s oceans are not only warming, but are furthermore acidifying through the reaction of seawater with carbon dioxide, measured in pH and termed ocean acidification. The aim of this thesis was to provide greater understanding of the impact of ocean acidification on one of the most important commercial species, the Atlantic cod (Gadus morhua) and to provide a quantitative foundation to evaluate recruitment processes of this species. This thesis has quantified the effect of ocean acidification on larval survival of two Atlantic cod stocks from the Western Baltic Sea and the Barents Sea and how this translates into the recruitment of these populations. Additionally, the effect of acidification and its interaction with food availability on larval growth was quantified for the Barents Sea cod. In order to investigate the potential for adaptation or acclimation, it was furthermore explored whether the acclimation of the parental generation to acidification had a significant effect on larval survival and organ development. The results of this dissertation demonstrate that ocean acidification may pose a severe threat to Atlantic cod populations. Nonetheless, the exact effects are very complex and rely on other factors, like the exposure of the parental generation to acidification and on food availability to the larvae. Im Verlauf des zwanzigsten und dem Beginn des einundzwanzigsten Jahrhunderts haben der technische Fortschritt in Verbindung mit einem starken Zuwachs in der Weltbevölkerung zu einem hohen Anstieg der Emissionen von Treibhausgasen wie Kohlenstoffdioxid geführt. Änderungen in der Chemie der Atmosphäre führen nicht nur zu ...